Tanaidacea (Crustacea: Peracarida) from the Southern French Polynesia Expedition, 2014. I. Tanaidomorpha - Bird, Graham J. (Zootaxa, 2019)
Shallow-water and littoral tanaids from the Southern French Polynesia Expedition, 2014 to Rapa Iti, Morane, Taravai and Mangareva, were examined with the tanaidomorphs represented by nine taxa, four of them described as new species within the genera Chondrochelia, Poorea, Triparatanais, and Zeuxoides. A new paratanaid genus is established, Periparatanais n. gen., and Nobili’s Tanais seurati is rediscovered and redescribed as a species distinct from the Hawai’ian Zeuxo insularis n. comb. A broad comparison of tanaid faunas across the Polynesian and eastern Indo-Pacific regions based on the Marine Ecosystems of the World (MEOW) classification shows almost no species-level correspondences but several genera within four apseudomorphan and three tanaidomorphan families are consistently present.